The theory of governance at Qudama bin Jaafar d. 337 AH / 948 AD In his book Al-Kharj and the writing industry - Sadiq, Ass.Prof Dr. Fadel Kadhim (Thi Qar Arts Journal, 2023)
The Muslims cared more than they cared for writing about the policy of managing the state and the system of governance required and the nature of the ruler and his moral qualities, and also how his assistants are from ministers and advisers and other employees, as well as the way the ruler reaches the seat of power. Many scholars of the Islamic nation at that time wrote about this, among them Qudamah bin Ja’far al-Baghdadi, who died in 337 AH / 948 AD, who devoted six chapters to talk about this topic in his book (The Tax and the Art of Writing) in the eighth (last) position, speaking in importance to the need of people to establish governance and what are the specifications of kings (rulers) and their responsibilities and how their relations with the people are. The research was divided into three topics: the first dealt with a brief biography of Qudamah bin Ja’far and his author (The Tax and the Art of Writing), and the second the human need for a system of governance, and the third in the morals of kings and the qualities of their employees from ministers and others from the royal court staff.